Design of robust output-feedback-based automatic steering controller for unmanned electric vehicles. (7th August 2019) - Li, Keqiang; Guo, Jinghua; Luo, Yugong
This paper presents a robust output-feedback-based automatic steering control scheme for unmanned electric vehicles (UEV). To address the challenging problem, an uncertain dynamic model of the UEV is firstly developed, in which the uncertainties in the tyre cornering stiffness and the actuator faults are included. Then, to deal with the uncertain features and actuator faults of UEV, a robust output-feedback-based control algorithm for automatic steering system of UEV is proposed to achieve the prescribed transient for path tracking errors while keeping all other closed-loop signals bounded. Finally, simulation and experimental results demonstrate that the proposed automatic steering control scheme can effectively improve the tracking performance of UEV.